ANALISIS DAMPAK PEMBANGUNAN ZONA INTEGRITAS TERHADAP KINERJA ORGANISASI MELALUI KUALITAS PELAYANAN PUBLIK DAN PERSEPSI ANTI KORUPSI (Kasus pada Perguruan Tinggi Negeri di Tasikmalaya) - Iqbal, Muhammad; Mulyana, Deden; Abdullah, Yusuf (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2024)
This reseacrh aims to determine the effect of integrity zone development on public service quality and anti-corruption perceptions; the effect of integrity zone development on organisational performance; and the effect of integrity zone development on organisational performance through public service quality and anti-corruption perceptions. This research was quantitative with a descriptive approach, using primary data and partial least squares structural equation model (PLS-SEM) analysis techniques. The results of this study concluded that there was a significant positive influence between the development of integrity zones on the quality of public services and anti-corruption perceptions; there was a positive and significant influence between the development of integrity zones on organisational performance; and there was a significant positive influence between the development of integrity zones on organisational performance through the quality of public services and anti-corruption perceptions. The implication is that the development of integrity zones in universities in Tasikmalaya has the potential to improve organisational performance through improving the quality of public services and accelerating anti-corruption efforts